Urgensi Pembahasan Taubat dalam Perspektif Hadis - muhammad nurbani (Holistic al-Hadis, 2019)
Humans are not beings who avoid mistakes and sin like an angel. And of course everyone has made a mistake. There is no one in this world who is free from mistakes. Therefore, God opens the door to repentance as much as possible for servants or people who regret and realize the mistakes they have made. Even though there are people who are free from sin"Ma'sum" are only a few people, and they are Apostles and Prophets. The rest will always be in a state between kindness andcrime. Until one day good will emerge as the winner who giveshumans become noble and noble beings. and at other times the evil will be the victor who brings the humiliation that ultimately falls into sin. Humans will not be free of deliberate or unintentional mistakes. So every human action must contain an element of error. God is very happy if His servants want to repent and God will forgive all the mistakes that have been made. And the best people who realize that they have done something wrong will immediately apologize to God through forgiveness and repentance. Faster, better before death comes. Repentance means remorse and returning to the right path. Repentance itself is a manifestation of the return of the Servant to accept God's commandment and explain the Prohibition.